Penerapan Guided Discovery untuk Meningkatkan Minat Belajar Siswa dengan Pemanfaatan Media Pembelajaran Canva pada Mata Pelajaran Informatika Kelas X Teknik Mesin SMK Semen Padang - Devi Nurul Maryam (Journal of Research and Investigation in Education, 2026)
This study aims to increase students' interest in learning by utilizing Canva learning media in informatics subjects for class X Mechanical Engineering at Semen Padang Vocational School. The method used in this study is classroom action research (CAR) which is a type of qualitative research that emphasizes the process, designed to achieve improvements in practice and real situations in the classroom in its implementation, this classroom action research consists of four steps, namely planning, implementing actions, observation results, and reflection (reflecting). The research subjects in class X TM 1 were 26 students. The results of classroom action research by applying the guided discovery method assisted by Canva media, it can be concluded that the application of the guided discovery method assisted by Canva media can improve students' abilities in identifying informatics material categories and by applying the guided discovery method assisted by Canva media can improve students' learning terminals during the learning implementation process with a significant increase in cycle I to cycle II by 38.3%.